THE RELATIONSHIP OF SKIPPING BREAKFAST WITH BODY MASS INDEX IN MAN 1 PALEMBANG STUDENTS - AFRIYANA Siregar; Yuli Hartati; Imelda Telisa (Proceeding B-ICON, 2023)
Breakfast is an eating and drinking activity carried out between waking up in the morning until 9 o'clock to meet some of the daily nutritional needs (15-30% of nutritional needs) in order to realize a healthy, active, physical, intelligent, mental, and emotional life very quickly. It is unfortunate that 26.1% of Indonesian children only consume drinks (water, tea, milk) and around 44.6% who are less or never have breakfast. The type of research used is quantitative research with a cross sectional design, namely data collection / observation is carried out at the same time. The population of this study were all students of MAN 1 Palembang. The sampling technique used was simple random sampling which is a sample taken randomly from the existing population. The sample in this study was 32 people. This research was conducted in June 2023. The data of this study were taken by direct interview to students and female students using questionnaires, food recall forms, and anthropometric measurements in the form of Height, Body Weight, Waist Circumference, and Hip Circumference.